Application of Orem's Self-Care Theory in Lowering Blood Pressure in Hypertension Patients Grade 1 Through Resistance Band Exercise and Almond Chocolate Consumption - Maulidia Selfianie; Suharsono Suharsono; Rr. Sri Endang Pujiastuti (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Self-care plays a critical role in the prevention and management of hypertension. This study aimed to evaluate the impact of Orem’s Self-Care Theory on blood pressure reduction through resistance band exercise and almond chocolate consumption in hypertension patients. A quasi-experimental pretest-posttest control group design was used. The study involved 76 respondents with hypertension grade 1, divided into intervention and control groups. The intervention group participated in resistance band exercises three times a week for 28 days and consumed almond chocolate, while the control group received standard antihypertensive treatment. Data analysis was conducted using the Wilcoxon and Mann-Whitney tests with α < 0.05. The results showed a significant reduction in both systolic (p = 0.000) and diastolic (p = 0.002) blood pressure in the intervention group. Resistance band exercises enhanced vascular endothelial function, while almond chocolate stimulated nitric oxide synthesis, leading to vasodilation. These intervention aligned with Orem’s Self-Care Theory, highlighting the importance of individual commitment to health. The innovative aspect of this study lies in its integrated approach, as it is among the first to combine Orem’s Self-Care Theory with both physical (resistance band exercise) and nutritional (almond chocolate consumption) interventions for hypertensive patients. The study concludes that applying Orem’s Self-Care Theory through exercise and dietary changes effectively reduces blood pressure in hypertensive patients. It is recommended that health practitioners incorporate these self-care practices alongside the Patient-Centered Care (PCC) concept to address individual needs. This integrated approach can enhance hypertension management, improve blood pressure control, and boost patient satisfaction, ultimately leading to better health outcomes.